PP.23.24: THE AA2-RATIO. (June 2015) - Poglitsch, M.; Schwager, C.; Van Oyen, D.; Aigner, C.; Domenig, O.
Abstract : Objective: Primary aldosteronism (PA) is severe form of hypertension characterized by strongly increased secretion of aldosterone mediated by adenomas or other forms of adrenal hyper-activity. Once detected, PA can be usually cured by either surgical intervention or by appropriate pharmacologic treatments. This is also reflected in clinical guidelines of Endocrine Societies in Europe and the US, suggesting extensive PA screening activities among resistant hypertensive patients. The incidence of PA among hypertensive patients varies strongly between different studies, which is in part caused by the complex state-of-the-art testing procedure that unfortunately is far away from being a versatile PA screening tool. Despite strong limitations regarding selectivity, sensitivity and the interference with multiple anti-hypertensive drugs, the aldosterone-renin-ratio (ARR) is widely used for PA case detection. Design and method: However, there is still a strong demand for accurate and reliable and patient friendly PA case detection. The use of novel and more accurate technologies for quantification of aldosterone and renin activity might help to improve the power of the ARR as a diagnostic tool for PA. However, there is still a big need for a versatile PA screening assay that doesn't interfere with anti-hypertensive treatments and therefore allows the clear identification of PA patients without complex corrections and adaptions being necessary and without increasing the patient's cardiovascular risk in the course of the diagnostic process. Results: The Aldosterone-to-Angiotensin-II-Ratio (AA2-Ratio) is a novel mass-spectrometry based high-throughput test for PA that combines the plasma levels of aldosterone and physiologically active angiotensin II into a diagnostic ratio. First data obtained in a proof-of-concept study investigating PA positive and negative patients proved the AA2-Ratio to be a powerful and cost-effective diagnostic tool for the diagnosis of PA in clinical practice. Conclusions: The test performance is superior to the ARR in terms of the diagnostic window and method accuracy. The AA2-Ratio does not interfere with standard anti-hypertensive drugs including ACE inhibitors and besides providing a diagnostic value for PA, the AA2-Ratio is can be used for compliance monitoring in patients treated with ACE blockers.